X-ray fluorescence (XRF) measurements of a Holocene sediment core from Limni Volvi, Greece - Ganz, Kathrin; van Vugt, Lieveke; Gobet, Erika; Morales-Molino, César; Giagkoulis, Tryfon; Ogi, Sarah; Hächler, Luc; Schaad, Emmanuel; Zander, Paul D; Lloren, Ronald; Dubois, Nathalie; Grosjean, Martin; et al. (PANGAEA, 2025)
In 2020 and 2021, we retrieved six parallel sediment cores from Limni Volvi, northern Greece (coring location: 40°39′51.40″N, 23°32′30.70″E), at a water depth of 19.3 m using a UWITEC piston corer (6 cm diameter). Here, we present X-ray fluorescence (XRF), hyperspectral imaging (HSI) and magnetic susceptibility (MS) measurements made on the 19.65 m long composite core. The investigated time interval covers the entire Holocene. The core sequence was analysed to reconstruct the environmental history and palaeoclimatic changes in the area during the Holocene. MS was measured at the Institute of Plant Sciences of the University of Bern at a 5-mm resolution, using a Bartington MS2E sensor. Elemental analysis of the sediment half-cores was performed at the Swiss Federal Institute of Aquatic Science and Technology (Eawag) with an AVAATECH XRF core-scanner (AVAATECH XRF Technology, Dodewaard, The Netherlands) with a resolution of 5 mm. Low-energy elements from Al to Fe were measured at 10 kV with 1500 A and no filter, and exposed for 15s. Mid-energy elements Cu to Mo were acquired using 30 kV setting, 2000 A, with Pd thin filter at 40 s count time. The X-ray was sourced using Oxford 100 Watt with a rhodium anode. The scanner had a Canberra X − PIPS/DSA 1000 (MCA) detector. HSI scans were performed at the Institute of Geography of the University of Bern using a Specim PFD-xx-V10E hyperspectral single core scanning system. The following settings were used for all scans: field of view: 109.33 mm; resolution: 0.0833 mm; exposure: 160 ms; tray speed: 0.5 mm s−1; frame rate: 6 hz; aperture: 1.9.
Keywords: Greece; hyperspectral imaging; Magnetic susceptibility; XRF core scanner data